Hypoalbuminemia as a marker of adverse outcome in children admitted to pediatric intensive care unit - Kumar, Sandeep; Aroor, Shrikiran; Kini, Pushpa Gurudas; Mundkur, Suneel; Moideen, Adel (Indian Journal of Child Health, 2018)
Background: Research on critically ill adult patients has shown the usefulness of albumin as a predictor of increased morbidity and mortality. There is a paucity of similar data in pediatric age group. Objective: The objective of the study was to know the incidence of hypoalbuminemia in children admitted to pediatric intensive care unit (PICU) and its correlation to disease severity and clinical outcome. Materials and Methods: This was a prospective observational study conducted at the PICU of a tertiary care hospital. Children of age group 1 month – 18 years admitted to the PICU were included in the study. Serum albumin levels were estimated at the time of admission to PICU. Pediatric index of mortality 2 (PIM2) scoring system was used to assess the severity of illness at admission and to calculate the predicted death rate (PDR). The independent sample t-test and Fisher’s exact test were used to compare the albumin levels with PDR and duration of hospital or PICU stay. Mortality risk was computed using Pearson’s Chi-square test. Multivariate regression analysis was performed to evaluate whether hypoalbuminemia is an independent predictor of mortality. Results: Mean serum albumin level in this study was 3.38±0.89 g/dL. The incidence of hypoalbuminemia was 44.1%. The PDR (calculated using PIM2 score) was increased in children with hypoalbuminemia compared with the normal albumin level group (p=0.004). As compared to children with normal albumin levels, children with hypoalbuminemia had longer duration of PICU stay (95% confidence interval (CI) for difference 0.86–3.03; p=0.05), higher need for ventilator support (odds ratio (OR) 4.2, p=0.003) and higher mortality (OR 0.16, p=0.002). The association of serum albumin levels with mortality remained significant even after adjusting for age and PDR by PIM2 score (OR=3.68; 95% CI, 1.76–7.74; p